Lost in the shadows: reflections on the dark side of co-production - Oli Williams; Sophie Sarre; Stan Constantina Papoulias; Sarah Knowles; Glenn Robert; Peter Beresford; Diana Rose; Sarah Carr; Meerat Kaur; Victoria J. Palmer (BMC, 2020)
Abstract This article is a response to Oliver et al.'s Commentary 'The dark side of coproduction: do the costs outweigh the benefits for health research?' recently published in Health Research Policy and Systems (2019, 17:33). The original commentary raises some important questions about how and when to co-produce health research, including highlighting various professional costs to those involved. However, we identify four related limitations in their inquiry, as follows: (1) the adoption of a problematically expansive definition of co-production that fails to acknowledge key features that distinguish co-production from broader collaboration; (2) a strong focus on technocratic rationales for co-producing research and a relative neglect of democratic rationales; (3) the transposition of legitimate concerns relating to collaboration between researchers and practitioners onto work with patients, service users and marginalised citizens; and (4) the presentation of bad practice as an inherent flaw, or indeed 'dark side', of co-production without attending to the corrupting influence of contextual factors within academic research that facilitate and even promote such malpractice. The Commentary's limitations can be seen to reflect the contemporary use of the term 'co-production' more broadly. We describe this phenomenon as 'cobiquity' - an apparent appetite for participatory research practice and increased emphasis on partnership working, in combination with the related emergence of a plethora of 'co' words, promoting a conflation of meanings and practices from different collaborative traditions. This phenomenon commonly leads to a misappropriation of the term 'co-production'. Our main motivation is to address this imprecision and the detrimental impact it has on efforts to enable co-production with marginalised and disadvantaged groups. We conclude that Oliver et al. stray too close to 'the problem' of 'co-production' seeing only the dark side rather than what is casting the shadows. We warn against such a restricted view and argue for greater scrutiny of the structural factors that largely explain academia's failure to accommodate and promote the egalitarian and utilitarian potential of co-produced research.